2020
DOI: 10.1177/0956797619896273
|View full text |Cite
|
Sign up to set email alerts
|

Two Preregistered Direct Replications of “Objects Don’t Object: Evidence That Self-Objectification Disrupts Women’s Social Activism”

Abstract: Self-objectification has been claimed to induce numerous detrimental consequences for women at the individual level (e.g., sexual dysfunction, depression, eating disorders). Additionally, at the collective level, it has been proposed that self-objectified women might themselves contribute to the maintenance of the patriarchal status quo, for instance, by participating less in collective action. In 2013, Calogero found a negative link between self-objectification and collective action, which was mediated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A wide amount of research demonstrated that self-objectification is linked directly and indirectly to several negative outcomes such as body shame, eating disorder, decreased personal a relational satisfaction, and impaired cognitive and physical performances (see Roberts et al, 2017, for a review). Although underdeveloped, other research suggests that, along with intraindividual and interpersonal consequences, self-objectification may also increase women’s acceptance of gender inequalities (e.g., Calogero & Tylka, 2014; Fox et al, 2015; but see De Wilde et al, 2020). In fact, perpetuating the existing gender-role norms in the sexual objectification system, women are valued for their physical attractiveness, while men are typically considered for their agency and performance (Choma & Prusaczyk, 2018; Zurbriggen, 2013).…”
Section: The Female Targets Perspective: Self-objectification and Att...mentioning
confidence: 99%
“…A wide amount of research demonstrated that self-objectification is linked directly and indirectly to several negative outcomes such as body shame, eating disorder, decreased personal a relational satisfaction, and impaired cognitive and physical performances (see Roberts et al, 2017, for a review). Although underdeveloped, other research suggests that, along with intraindividual and interpersonal consequences, self-objectification may also increase women’s acceptance of gender inequalities (e.g., Calogero & Tylka, 2014; Fox et al, 2015; but see De Wilde et al, 2020). In fact, perpetuating the existing gender-role norms in the sexual objectification system, women are valued for their physical attractiveness, while men are typically considered for their agency and performance (Choma & Prusaczyk, 2018; Zurbriggen, 2013).…”
Section: The Female Targets Perspective: Self-objectification and Att...mentioning
confidence: 99%